Prenatal Diagnosis and Postnatal Findings of Cephalothoracopagus Janiceps Disymmetros: A Case Report. (29th May 2012) - Rios, Lívia Teresa Moreira; Araujo Júnior, Edward; Nardozza, Luciano Marcondes Machado; Nacaratto, Daniela Cristina; Moron, Antonio Fernandes; Martins, Marília da Glória
Abstract : Conjoined twins are rare variants of monozygotic twins, which result from an incomplete division of the embryonic disk. Cephalothoracopagus is a rare twin pregnancy described as imperfect fusion of the head and chest, but separated columns, limbs, and pelvis. They occur with incidence rates that range from 1 per 50, 000 to 1 per 100, 000 births; however, the incidence of the cephalothoracopagus variety is 1 per 58 conjoined twins. In the case of identical and symmetric faces caused by the orientations of the 2 notochordal axes that are perfectly ventroventral, they are called janiceps disymmetros. We present a prenatal diagnosis of a typical case of cephalothoracopagus janiceps disymmetros and the diagnostic confirmation by image and pathology exams.